2001
DOI: 10.1097/00000658-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12 Secretion Enhances Antitumor Efficacy of Oncolytic Herpes Simplex Viral Therapy for Colorectal Cancer

Abstract: ObjectiveTo assess the strategy of combining oncolytic herpes simplex virus (HSV) therapy with immunomodulatory therapy as treatment for experimental colon cancer. The oncolytic HSV recombinant NV1023 and the interleukin 12 (IL-12)-secreting oncolytic NV1042 virus were evaluated in vitro and in vivo with respect to antitumor efficacy. Summary Background DataGenetically engineered, replication-conditional, attenuated HSVs have shown oncolytic activity against a wide variety of solid malignancies. Other strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 40 publications
(37 reference statements)
1
58
0
Order By: Relevance
“…While a number of cytokines have been considered for use in anti-tumour therapy (including the use of GM-CSF or IL12 in oncolytic HSV vectors [39][40][41][42][43] ), GM-CSF has generally, and most reliably, given the best results when tested in comparison to other cytokines in pre-clinical models. Clinically, for cancer treatment, indications of efficacy have also been seen when GM-CSF has been delivered by a number of means (eg using engineered, re-injected primary tumour cells -'GVAX'; eg reference 44).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of cytokines have been considered for use in anti-tumour therapy (including the use of GM-CSF or IL12 in oncolytic HSV vectors [39][40][41][42][43] ), GM-CSF has generally, and most reliably, given the best results when tested in comparison to other cytokines in pre-clinical models. Clinically, for cancer treatment, indications of efficacy have also been seen when GM-CSF has been delivered by a number of means (eg using engineered, re-injected primary tumour cells -'GVAX'; eg reference 44).…”
Section: Discussionmentioning
confidence: 99%
“…A number of preclinical studies have shown that oncolytic herpes viruses induce cytotoxic T lymphocyte-mediated antitumor immunity, which can inhibit tumor regrowth upon rechallenge. [33][34][35][36] Consistent with this, efforts have been made to arm oncolytic herpes viruses with cytokines such as interleukin-12 37 and granulocyte-macrophage colony-stimulating factor 10,38 in order to intensify antitumor immunity. From this perspective, it might be said that the potency of a virus relies on its capacity to induce antitumor immunity.…”
Section: Introductionmentioning
confidence: 92%
“…Preliminary work suggests that combined immunostimulatory and oncolytic therapy enhances tumor cell kill. 33 In the present experiments, NV1042, a replication competent, oncolytic HSV expressing IL-12, was used to treat established hepatic tumors prior to resection. IL-12 was chosen because of its broad and potent immunostimulatory activity.…”
mentioning
confidence: 99%